2019
DOI: 10.4040/jkan.2019.49.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mobile Navigation Program in Colorectal Cancer Patients based on Uncertainty Theory

Abstract: This study aimed to examine the effects of a mobile navigation program on uncertainty, resilience, and growth through uncertainty in colorectal cancer patients. Methods: To verify the effectiveness of the mobile navigation program, 61 participants diagnosed with colorectal cancer undergoing surgery were selected. A nonequivalent control group nonsynchronized design was used to evaluate the program. Uncertainty was measured using the Korean version of the Uncertainty in Illness Scale, resilience was measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…For the current study's participants, considering that an average of 26 months had passed since the initial diagnosis, it can be assumed that they developed a new perspective that accepts uncertainty as a natural part of life. For patients with colorectal cancer who evaluated uncertainty as danger, a mobile navigation program was structured around the enhancement of nursing continuity and empowerment and was effective for growth through uncertainty [37]. Long-term exposure to uncertainty can lead to intrusive thinking, avoidance, and severe emotional distress [11].…”
Section: Discussionmentioning
confidence: 99%
“…For the current study's participants, considering that an average of 26 months had passed since the initial diagnosis, it can be assumed that they developed a new perspective that accepts uncertainty as a natural part of life. For patients with colorectal cancer who evaluated uncertainty as danger, a mobile navigation program was structured around the enhancement of nursing continuity and empowerment and was effective for growth through uncertainty [37]. Long-term exposure to uncertainty can lead to intrusive thinking, avoidance, and severe emotional distress [11].…”
Section: Discussionmentioning
confidence: 99%
“…Our trial shows that the MGCS program significantly decreased the uncertainty in patients with GC at 24 weeks. This is consistent with that reported in another study, which found that a mobile navigation program significantly decreased the uncertainty in patients with colorectal cancer [ 22 ]. During chemotherapy, patients with GC may feel ambiguous about what to expect from their illness and treatment because they are not provided with clear, credible, and sufficient information [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous research on a face-to-face uncertainty management intervention reduced uncertainty in illness for patients with HIV with an effect size of 0.53 [ 21 ]. Another study reported that a mobile navigation program reduced uncertainty in illness for patients with colorectal cancer with an effect size of 0.49 [ 22 ]. Thus, the effect size (0.49) of web-based intervention for patients with cancer was used to determine the sample size.…”
Section: Methodsmentioning
confidence: 99%
“…Previous online interventions did not evaluate the effect size of uncertainty in illness for participants with gynaecological cancer. Similar research on a mobile navigation program reported a medium effect size for uncertainty in illness for participants with colorectal cancer (Cohen's d =.49) (Kim & Park, 2019). To achieve a 0.80 power and a 0.05 significance level, this study will need a minimum of 134 participants (67 in each group).…”
Section: The Studymentioning
confidence: 72%